The Spatial Continuation of Englishness in H. G. Wells’s Men Like Gods (Philologia, 2021)
This paper examines continuities and ruptures between England and Utopia on the level of spatiality in H. G. Wells’s Men Like Gods (1923). In designating the possibility of time travel, similar to The Time Machine, Wells enforces the idea of indiscrete space where Utopia has become England’s spatial continuation. In line with Wells’s bifocal perspective on England, which balances between a sentimental and yet detached depiction, and uncompromising visions of destruction, Utopia is construed of both clearness and dissent. Through the image of and debates about the Crystal Palace, it is sustained that the concept of Utopia is closely linked to Wells’s anti-entropic impulses and evolutionary gradualism. It is concluded that, equipped with the means of locomotion, traditions of freedom, and the discourse of “progress with continuity”, the English identity is appropriately geared to a continuous transition into Utopia.
Keywords: utopia; England; Englishness; national identity; spatial continuity; entropy